Resuscitation After Hemorrhagic Shock in the Microcirculation: Targeting Optimal Oxygen Delivery in the Design of Artificial Blood Substitutes - Munoz, Carlos; Aletti, Federico; Govender, Krianthan; Cabrales, Pedro; Kistler, Erik B. (Frontiers in Medicine, 2020)
Microcirculatory preservation is essential for patient recovery from hemorrhagic shock. In hemorrhagic shock, microcirculatory flow and pressure are greatly reduced, creating an oxygen debt that may eventually become irreversible. During shock tissues become hypoxic, cellular respiration turns to anaerobic metabolism, and the microcirculation rapidly begins to fail. This condition requires immediate fluid resuscitation to promote tissue reperfusion. The choice of fluid for resuscitation is whole blood; however, this may not be readily available and on a larger scale, may be globally insufficient. Thus, extensive research on viable alternatives to blood has been undertaken in an effort to develop a clinically deployable blood substitute, this has not, as of yet achieved fruition, in part due to an incomplete understanding of the complexities of the function of blood in the microcirculation. Hemodynamic resuscitation is acknowledged to be contingent on a number of factors other than volume expansion. The circulation of whole blood is carefully regulated to optimize oxygen delivery to the tissues via shear stress modulation through blood viscosity, inherent oxygen carry capacity, cell-free layer variation, and myogenic response, among other variables. Although plasma expanders can address a number of these issues, hemoglobin-based oxygen carriers (HBOCs) introduce a method to replenish the intrinsic oxygen carrying capacity of blood. There continue to be a number of issues related to HBOCs, but recent advances in the next generation HBOCs show promise in preservation of microcirculatory function and limiting toxicities. Development of HBOCs is now focused on viscosity and the degree of microvascular shear stress achieved in order to optimize vasoactive and oxygen delivery responses by leveraging the restoration and maintenance of physiological responses to blood flow in the microcirculation. Blood substitutes with higher viscous properties tend to improve oxygen delivery compared to those with lower viscosities. This review details current concepts in blood substitutes, particularly as they relate to trauma/hemorrhagic shock, with a specific focus on their complex interactions in the microcirculation.